The Unpostponable Incorporation of the Gender Perspective into Architectural Education in the 21st Century - Mónica Sánchez Bernal; Carolina Blanco (Dearq)
Teaching serves as a tool for shaping society by guiding the training of students, incorporating different perspectives across disciplinary fields, and reflecting the era's characteristics or the transformations it seeks to achieve. This article presents the experiences and reflections from the course "Arquitectura con enfoque de género y diferencial" (Architecture with a Gender and Differential Perspective), a pioneering initiative in urban-architectural design implemented as part of the undergraduate program at Universidad de los Andes in 2022 and 2023. The course is grounded in the belief that integrating these perspectives into practice and research can improve quality of life for women and diverse people, fostering inclusive, habitable, empathetic, and safe physical-spatial environments.